“Sistema de Control Interno para el Mejoramiento en las Ventas de la Empresa Dina Diésel del Cantón La Maná”. - Calero Lucio, Zoila Margarita (2020)
At present, internal control within companies constitutes a fundamental axis for their development, because it allows those responsible for an organization, to have adequate control and the reliability of the procedures executed, to achieve the proposed objectives, is by This was considered essential for the company Dina Diesel to have an evaluation of the internal control system for the improvement of its sales. Being necessary for this the application of the types of research: exploratory, descriptive, bibliographic and inductive, deductive, analytical research methods and the techniques of observation, interview and surveys through a list of questions focused on collecting information on the level of compliance with policies and procedures in sales in the company. The diagnosis of the current situation and the level of compliance with policies and procedures in sales in the company, through an interview with the owner and you find the employees, it was known that a functional structure, policies, mission, has not been established. vision, objectives, values, organization manuals and functions, in a documented manner; In addition, there is no monitoring system for customer complaints and disagreements. Therefore, the design of an internal control manual was considered essential through the COSO I model that was structured by: the mission statement, vision, values, SWOT analysis, structural organizational chart, functional organic for the sales area, flow grams of the sales process, achievement indicators, macro internal control processes, the internal control questionnaire. The evaluation of the internal control allowed to demonstrate a level of confidence of 70% and a risk of 30% for the control environment component, the evaluation component reflected a level of confidence of 50% and a risk of 50%, the activities of control was placed with a level of confidence of 50% and a risk of 50%, with regard to information and communication the risk was 33% and the supervision and monitoring activities with a level of confidence of 67% and a 33% risk. The recommendations issued against each finding detected will contribute to improving the sales procedures in the organization, directly benefiting the owner, employees and customers of the Dina Diesel Company of The Mana canton.